Headache and Genetics - Betül Baykan (Türk Nöroloji Dergisi, 2006)
Migraine is considered as a complex polygenic disease in which the genetic factors interact with the environmental factors. There is a variety of evidence emphasizing that genetic factors take more role in migraine with aura than migraine without aura. Responsible loci, predisposition genes and their number remain to be unknown. The autozomal dominantly inherited monogenic migraine form, which is called as familial hemiplegic migraine, is now proved to be definitely caused by mutations in the genes related to the calcium channel (CACNA1A), Na-K-ATPase pump (ATP1A2) and the sodium channel (SCN1A). These data support the idea that migraine is a channelopathy, that is, an ion channel disease. Another interesting dimension of this phenomenon is that migraine without aura or totally normal phenotype can be found in some family members who inherit these mutations. On the other hand, two of these genes -that were discovered first- were investigated and found to form no significant predisposition region for the other common migraine phenotypes except for a few cases. Interestingly, in several trials, it has been determined that a locus in the 19p13 region, telomeric neighbor of this gene, has an association with the predisposition for migraine with aura; however this region is different from CACNA1A. The linkage analysis studies have shown distinct linkage regions on quite different chromosomes; the results of some studies has not been verified by others due to the methodological reasons and more importantly for the ethnical diversities. Numerous studies that investigate the association of the genes –that can be considered as candidates- with polymorphism are available, but their significance is not yet clear. The fact that in the future migraine genetics research will clarify the genes of common and serious forms is important in terms of specific diagnosis and treatment. It is important that migraine, which is considered by the World Health Organization not only as one of the most serious causes of disability but also as a personal and social problem, is investigated by each society with regard to its own genetic factors due to the intersociety d i f f e r e n c e s